Relative Differences in Concentration Levels during Sawing and Drilling of Car Bumpers Containing MWCNT and Organic Pigment. Issue 2 (5th January 2019) - Kuijpers, Eelco; Pronk, Anjoeka; Koivisto, Antti Joonas; Jensen, Keld Alstrup; Vermeulen, Roel; Fransman, Wouter
Abstract: Introduction: Knowledge on the exposure characteristics, including release of nanomaterials, is especially needed in the later stages of nano-enabled products' life cycles to perform better occupational risk assessments. The objective of this study was to assess the concentrations during sawing and drilling in car bumpers containing multi-walled carbon nanotubes (MWCNTs) and nanosized organic pigment (OP) under variable realistic workplace situations related to the ventilation in the room and machine settings. Methods: Twelve different experiments were performed in triplicate ( N = 36) using tools powered by induction engines that allow interference-free particle measurements. A DiSCmini was used to measure particle number concentrations, whereas particle size distributions were measured using Aerodynamic Particle Sizer (TSI), Scanning Mobility Particle Sizer (TSI), and Electrical Low Pressure Impactor (Dekati). In addition, inhalable particles were sampled using IOM samplers on filters for scanning electron microscope/energy-dispersive X-ray spectrometry (SEM/EDX) analyses. Data were analysed to estimate the effects of individual exposure determinants, in a two-stage modelling strategy using Autoregressive Integrated Moving Average models (stage 1) and subsequently combining first stage results in simulations using multiple linear regression models (stage 2). Results: In sawing experiments, partly melted carbon-rich particles (mainly 2 to 8 µm) were identified with SEM/EDX, whereas drilling experiments revealed no activity-related particles. In addition, no pristine engineered nanoparticles (MWCNTs and OP) were observed to be liberated from the matrix. Statistical analyses showed significant effects of a higher sawing speed, a reduction in air concentration due to mechanical ventilation, and less exposure during sawing of car bumpers containing MWCNTs compared to bumpers containing OP. Conclusion: The experiments in this study give an indication of the effects of different abrasive activities (sawing, drilling), machine settings (sawing speed, drill size), mechanical ventilation, and material characteristics on the manufactured nano-objects, their agglomerates, and aggregates concentration levels.